Aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups: synthesis and characterization - Bapat, Snehalata P.; Jadhav, Sushilkumar A.; Valsange, Nitin G.; Tawade, Bhausaheb V.; Honkhambe, Pandurang N.; Chavan, Nayaku N.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2017)
A new bisphenol, 1,1-bis-[(4-hydroxyphenyl)-1-(4-phenylsulfonyl) phenyl)] ethane (DPSBP) was synthesized starting from diphenylsulfide and was characterized by spectroscopic methods. DPSBP was polycondensed with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of IPC and TPC (50: 50 mol%) by phase-transfer catalysed interfacial polymerization method to obtain aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups. A series of copolyesters was also obtained by polycondensation of varying molar proportions of DPSBP and bisphenol-A (BPA) with TPC. (Co) polyesters exhibited inherent viscosities in the range 0.56-1.57 dLg(-1) and number average molecular weights (Mn) were in the range 28,650-80,230 g/mol. Polyesters dissolved readily in common organic solvents such as dichloromethane, chloroform, tetrahydrofuran and aprotic polar solvents such as N-methylpyrrolidone, and N, N-dimethylacetamide. Tough, transparent and flexible films of polyesters could be cast from their chloroform solutions. X-Ray diffraction studies indicated amorphous nature of aromatic polyesters. Polyesters showed T-g values in the range 223-257 degrees C while T-10 values were in the range of 469-484 degrees C indicating their excellent thermal stability.
Keywords: Aromatic polyesters; Bulky pendent group; solubility; thermal stability